Doses e fontes de nitrogênio na recuperação de pastagem de capim-Marandu em solo de cerrado - Costa, Kátia Aparecida de Pinho (2007)
The nitrogen has been indispensable in pasture formation, maintenance and recovery, being that its deficiency is one of the main causes of cultivated pasture degradation, mainly of Brachiaria genus. In this sense, the research was made considering the importance of nitrogen fertilization in degraded areas of pasture: to evaluate the dry mass production, and crude protein concentration, fiber in neutral and acid detergents, concentration of nutrients, nitrogen nutrition and any soil chemical attributes, under nitrogen doses and sources of marandu palisadegrass, by three years period. The experiment was carried out from July 2003 to March 2006 in the Farm Model belonging to the Course of Zootecny of the State University of Goiás, in a Typic Haplorthox clay texture soil argillous dystrophic Red Latosol. The experimental delineation used was a randomized complete block design, with three repetitions. In the main parcels one 2 x 4 factorial was used being two nitrogen sources (sulfate of ammonium and urea) and four nitrogen doses (0, 100, 200 and 300 kg ha-1 year-1). In sub parcels were studied the three years (2004, 2005 and 2006) in reference to the time of pasture evaluation. In each year, the nitrogen fertilization was parceled out at three times, after each cutting evaluation. Three forage plants cuts per year had been carried through. Nitrogen application was determinant for marandu palisadegrass recuperation. Higher nitrogen doses promoted increasings on dry mass production and reduction on fiber concentration in neutron and acid detergents. Ammonium sulfate resulted in higher dry mass production than in urea in all evaluated doses and years. Nitrogen, potassium, magnesium, sulfur, copper, iron and N:S relationship were higher by using nitrogen applied in soil. Increasings nitrogen doses promoted reduction in leaf phosphorus. The SPAD and leaf Nitrogen concentration in leaf of marandu palisadegrass just expanded presented a direct relation among these variations. Increasing nitrogen doses of both sources promoted reduction in soil pH and increasings in exchangeable aluminum, organic matter, total nitrogen, nitric and ammoniac nitrogen in 0-20 and 20-40 soil depth.